Image Processing Algoritm of The Red Chili Plant Using Three Dimensional Vision Sensor - I Dewa Made Subrata; Danang Suganjar (Jurnal Keteknikan Pertanian, 2002)
Machine vision is one of the image processing techniques used to process the image of an object according to its color, shape, size by using a video camera as an image capturer. The image processing used in this study, could be categorized as one of the machine vision techniques, eventhough using three dimensional vision sensor as an image capturer.The three dimensional vision sensor constructed using two laser beams namely the red laser (685 nm) and the infrared laser (830 nm) as the light transmitter and tow position sensitive device (PSDs) as the receiver unit. The output signals of each PSD were detected from two output terminals called anode A and anode B. Three kind of signals namely red A+B, infrared A and infrared B were collected the red ripe chili fruits from their canopy and to calculate the cutting point of the individual fruit's stem three dimensionally.